Fiscal Transfers and the Persistence of Regional Inequality: A Critical Review of Indonesia's Intergovernmental Funding System - Paulina; Adiawaty, Susi (Moneta : Journal of Economics and Finance, 2025)
This study critically examines the effectiveness of Indonesia’s intergovernmental fiscal transfer mechanisms primarily the General Allocation Fund (DAU) and the Special Allocation Fund (DAK) in addressing persistent regional inequality since the implementation of the post Otonomi Daerah decentralization reforms. The research aims to assess whether these fiscal instruments have fulfilled their redistributive mandate and to identify structural and governance related barriers that limit their impact. Employing a mixed-method approach with secondary data, the study analyzes fiscal gaps, transfer effectiveness, and regional disparities. The analysis combines statistical indices (Gini coefficient, Theil index) with case studies from West Sumatra, East Java, and Eastern Indonesia, complemented by international comparisons and policy evaluations. The findings show that DAU and DAK have expanded fiscal flows to poorer regions but remain constrained by formulaic designs that overlook socio-economic diversity. Administrative inefficiencies, weak planning capacity, and limited accountability reduce fund utilization. Comparative international models suggest alternatives through performance-based and needs-responsive allocation formulas. In conclusion, Indonesia's fiscal transfer framework must evolve from a volume based to an outcome driven model. By incorporating equity sensitive criteria, decentralizing planning autonomy, and strengthening transparency, fiscal transfers can transition from redistributive tools to transformative instruments that narrow regional inequality and foster inclusive national development.